2020
DOI: 10.1074/jbc.ra119.011185
|View full text |Cite
|
Sign up to set email alerts
|

The noncanonical small heat shock protein HSP-17 from Caenorhabditis elegans is a selective protein aggregase

Abstract: Small heat shock proteins (sHsps) are conserved, ubiquitous members of the proteostasis network. Canonically, they act as “holdases” and buffer unfolded or misfolded proteins against aggregation in an ATP-independent manner. Whereas bacteria and yeast each have only two sHsps in their genomes, this number is higher in metazoan genomes, suggesting a spatiotemporal and functional specialization in higher eukaryotes. Here, using recombinantly expressed and purified proteins, static light-scattering analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
5
14
0
Order By: Relevance
“…The most impressive demonstration of the significance of sHsp homologs appears to be in C. elegans where the lifespan prolongation in the ultra-long-lived insulin resistant daf-2 mutant was dependent on protein aggregates containing the CryAB homolog Hsp16.1 (Walther et al, 2015). Furthermore, recent work indicates that a non-canonical sHsp (Hsp-17) functions as an "aggregase" and loss of function mutants have shorter lifespan (Iburg et al, 2020). Similarly, the yeast analog Hsp42, harboring a prion-like domain in the N-terminus, is endowed with both chaperone and aggregase functions (Grousl et al, 2018).…”
Section: Cryab and Shsps Through Evolution: The Long And Winding Roadmentioning
confidence: 99%
“…The most impressive demonstration of the significance of sHsp homologs appears to be in C. elegans where the lifespan prolongation in the ultra-long-lived insulin resistant daf-2 mutant was dependent on protein aggregates containing the CryAB homolog Hsp16.1 (Walther et al, 2015). Furthermore, recent work indicates that a non-canonical sHsp (Hsp-17) functions as an "aggregase" and loss of function mutants have shorter lifespan (Iburg et al, 2020). Similarly, the yeast analog Hsp42, harboring a prion-like domain in the N-terminus, is endowed with both chaperone and aggregase functions (Grousl et al, 2018).…”
Section: Cryab and Shsps Through Evolution: The Long And Winding Roadmentioning
confidence: 99%
“…Luciferase assay was performed according to previously published protocols 47 , 50 . Briefly, a 15 nM luciferase solution in 1× dilution buffer (50 mM HEPES pH 7.4, 100 mM KCl, 5 mM MgCl 2 , 1 mM DTT, 10 µM BSA, 3.5 µM Pyruvate Kinase (Sigma-Aldrich, #P7768), 3 mM Phosphoenol Pyruvate) was denatured at 45 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, proteins in the HSP-16 family act as passive ligands to prevent aggregation and are known to be upregulated under conditions of oxidative stress 78 as well as during treatment with protein damaging compounds 79 . HSP-17 has been shown to prevent aggregation of specific proteins, although its mechanism of action remains unclear 80 . Previous studies have shown that sHSPs are upregulated in many long-lived mutants including daf-2 81,82 , which is consistent with the observation that increased proteostasis protects from aging.…”
Section: Bmentioning
confidence: 99%